Introduction: The Betrayal of the Humanities under National Socialism - Levinson, Bernard M. (The betrayal of the humanities, 2022)
Levinson and Ericksen provide a substantive historical analysis of how and why academics under National Socialist rule in Germany collaborated directly or indirectly with the Nazi regime, betraying the values of their discipline. They ground their analysis on the German university as historically the embodiment of the Enlightenment values of the academic humanities. They investigate how individual scholars, particular departments, and entire universities collaborated with the Nazi regime. They examine the legacy of this era on higher education in Germany, including the process of Entnazifierung and the postwar rebuilding of the German university. The chapter provides a history of holocaust studies within scholarship. The volume also looks at the position of many German scholars in the post-war world having to defend their own work, or the work of their mentors, while simultaneously appearing not to accept Nazism.